PERGESERAN PERANAN DATUK PUTIO DALAM KEHIDUPAN MASYARAKAT SUKU PILIANG SUNGAI TONANG KENEGERIAN RUMBIO KABUPATEN KAMPAR - Yuhasbilal Yuhasbilal; Marwoto Saiman; Ridwan Melay (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: In the society in Kenegerian Rumbio Ninik mamak has its own order considering there are some tribes that are in the community. People who have tribal Ninik mamak piliang then be referred to as Datuok Putio (Datuk White), the tribal community called Datuk Godang Domo, Pitopang tribal community called Datuk Ulaksimano, Chaniago tribe known as Datuk Gindoh Malano, and Kampai tribe called Datuk Paduko. This study aims to determine (1) The procedure for the selection and appointment of Datuk Putio (2) The role of progenitor Putio in public life Tribe Piliang River Tonang under the provisions of Indigenous previously (3) Shape shifting role of Datuk Putio at the present time (4) The public perception Tribe Piliang river Tonang of adherence levels of society to Datuk Putio (5) factors - factors that causes occurrence Datuk Putio Shifting role in public Life Piliang river Tribe Tonang in Kenegerian Rumbio (6) measures that can be done to restore the role of Datuk Putio. This study uses qualitative research approach to history (History) and data collection techniques such as observation, interviews and documents or literature. Informant in this research is Datuk Putio and Tribal communities Piliang Tonang River. The results showed that Datuk Putio role in public life Tribe Piliang Tonang River at the present time has experienced a shift from customary provisions previously.Keywords: Role, Datuk Putio, Piliang River Tribe Tonang